Photocatalytic Treatment of Synthetic Wastewater Containing 2,4 dichlorophenol by Ternary MWCNTs /Co-TiO2 Nanocomposite Under Visible Light - Shahryar Nazarpour Laghani; Azadeh Ebrahimian Pirbazari (Journal of Water and Environmental Nanotechnology, 2017)
In this work, multi-walled carbon nanotubes (MWCNTs)/Co-TiO2 nanocomposites were synthesized and investigated for photocatalytic degradation of 2,4-dichlorophenol (2,4-DCP) under visible light. Characterization of photocatalysts was done by means of XRD, FT-IR and SEM/EDX techniques. Obtained results showed cobalt doping can inhibit phase transformation from anatase to rutile and eliminate the recombination of electron-hole pairs. The presence of MWCNTs can both increase the photoactivity and change surface properties to achieve sensitivity to visible light. The optimum mass ratio of MWCNTs and cobalt (Co) dopant in TiO2 was the prominent factor to harvest MWCNTs/Co-TiO2 photocatalyst. The sample containing 3.13 wt% cobalt exhibited the highest activity under visible light for 2,4-DCP degradation, which was completed within 180 min using a 0.1 g/L dose of this photocatalyst in a 40 mg/L solution of the 2,4-DCP. The reactions follow the first-order kinetics. The reaction intermediates were identified by GC–MS technique. GC–MS analysis showed the major intermediates of 2,4-DCP degradation are simple acids like oxalic acid, acetic acid, etc. as the final products.